Cyclophilin D Contributes to Anesthesia Neurotoxicity in the Developing Brain - Zhang, Yiying; Lu, Pan; Liang, Feng; Liufu, Ning; Dong, Yuanlin; Zheng, Jialin Charles; Xie, Zhongcong (Frontiers in Cell and Developmental Biology, 2020)
Anesthetic sevoflurane induces mitochondrial dysfunction, impairment of neurogenesis, and cognitive impairment in young mice, but the underlying mechanism remains to be determined. Cyclophilin D (CypD) is a modulatory factor for the mitochondrial permeability transition pore (mPTP). We, therefore, set out to evaluate the role of CypD in these sevoflurane-induced changes in vitro and in young mice. Wild-type (WT) and CypD knockout (KO) young (postnatal day 6, 7, and 8) mice received 3% sevoflurane 2 h daily and the neural progenitor cells (NPCs) harvested from the WT or CypD KO mice received 4.1% sevoflurane. We used immunohistochemistry and immunocytochemistry imaging, flow cytometry, Western blot, RT-PCR, co-immunoprecipitation, and Morris Water Maze to assess the interaction of sevoflurane and CypD on mitochondria function, neurogenesis, and cognition in vitro and in WT or CypD KO mice. We demonstrated that the sevoflurane anesthesia induced accumulation of CypD, mitochondrial dysfunction, impairment of neurogenesis, and cognitive impairment in WT mice or NPCs harvested from WT mice, but not in CypD KO mice or NPCs harvested from CypD KO mice. Furthermore, the sevoflurane anesthesia reduced the binding of CypD with Adenine nucleotide translocator, the other component of mPTP. These data suggest that the sevoflurane anesthesia might induce a CypD-dependent mitochondria dysfunction, impairment of neurogenesis, and cognitive impairment in young mice and NPCs.